Construção e validação de teste de associação implícita para preferência de compra entre propagandas com e sem apelo sexual - Costa, Marco Antonio de Oliveira (2019)
In today's world, companies face the great challenge of building sales strategies to create value for their brands, thus using sexual appeal in their advertisements to attract the attention of consumers to their goods and services. The Implicit Association Test (TAI) is shown as an attempt to access consumer preferences through automatic processing. The objective of the study was to construct and validate an implicit association test for preference between sexual and non-sexual advertisements. The sample consisted of 60 university students, 30 males and 30 females with a mean age of 24.77 years. Data collection took place in two stages, the first one in the classroom where participants answered the sociodemographic questionnaire, Sex Dependence Tracking Scale, Richmond Compulsive Purchase Scale and Visual Preference Scale for Preference of Propaganda (EVAPP). In the second stage, a web page address was sent to perform the TAI Preference Propaganda (TAIPP) for each participant, in two moments with a time interval of one week between the two measures. Half of the sample started the study by the explicit instruments and then performed the IAT, and the other participants did the reverse. In the retest condition the participants responded only to the IAT. Correlations were made between the TAI and the instruments used. There was a strong association between the "taste" and "appellate" categories in the test and retest conditions in the total sample, and gender difference, with men showing a greater association. TAIPP was a better predictor of preference than EVAPP. There was a strong positive correlation in the TAIPP test and retest conditions, indicating the reliability and validity of the instrument. TAIPP has been sensitive in capturing consumers' preference by allowing the prediction of consumer behavior from appealing advertisements.